Analysis of Atmospheric Lability in Heavy Rain Events in the South Bali Region (Case Study: Flood Events 5 and 6 December 2021) - Firdausi, Anin Nuril; Yuliara, I Made; Sumaja, Kadek; Suarbawa, Komang Ngurah; Suardana, Putu; Putra, I Ketut (BULETIN FISIKA, 2024)
An analysis of the occurrence of atmospheric lability was carried out when heavy rains occurred in the South Bali region, namely when a flood occurred on December 5 and 6 2021. The purpose of this research was to determine the atmospheric conditions based on weather parameters and atmospheric lability in three areas of South Bali, namely the City Denpasar, Tabanan Regency and Badung Regency. The research data is secondary data including synoptic observation data of rainfall intensity on 5-6 December 2021, ECMWF Reanalysis data, Himawari Satellite imagery data, and upper air observation data (Radiosonde). These data were analyzed based on local weather factors and atmospheric lability. It was found that on December 5, 2021, the air temperature in the atmosphere was relatively high at 14 o'clock. 00 WITA with relative humidity ranging from 82%-88% and relatively low on December 6 at the same hour with relative humidity decreasing to 78%. The wind speed has increased to 12.8 Knots from 5 to 6 December and atmospheric lability has changed by 94.3%. Even so, there is still rain with moderate intensity accompanied by thunderstorms.